Left ventricular dysfunction in COPD without pulmonary hypertension. - Janne M Hilde; Jonny Hisdal; Ingunn Skjørten; Viggo Hansteen; Morten N Melsom; Ole J Grøtta; Milada C Småstuen; Ingebjørg Seljeflot; Harald Arnesen; Sjur Humerfelt; Kjetil Steine (PLoS ONE)
Objectives We aimed to assess prevalence of left ventricular (LV) systolic and diastolic function in stable cohort of COPD patients, where LV disease had been thoroughly excluded in advance. Methods 100 COPD outpatients in GOLD II-IV and 34 controls were included. Patients were divided by invasive mean pulmonary artery pressure (mPAP) in COPD-PH (≥25 mmHg) and COPD-non-PH (<25 mmHg), which was subdivided in mPAP ≤20 mmHg and 21-24 mmHg. LV myocardial performance index (LV MPI) and strain by tissue Doppler imaging (TDI) were used for evaluation of LV global and systolic function, respectively. LV MPI ≥0.51 and strain ≤-15.8% were considered abnormal. LV diastolic function was assessed by the ratio between peak early (E) and late (A) velocity, early TDI E´, E/E´, isovolumic relaxation time, and left atrium volume. Results LV MPI ≥0.51 was found in 64.9% and 88.5% and LV strain ≤-15.8% in 62.2.% and 76.9% in the COPD-non-PH and COPD-PH patients, respectively. Similarly, LV MPI and LV strain were impaired even in patients with mPAP <20 mmHg. In multiple regression analyses, residual volume and stroke volume were best associated to LV MPI and LV strain, respectively. Except for isovolumic relaxation time, standard diastolic echo indices as E/A, E´, E/E´ and left atrium volume did not change from normal individuals to COPD-non-PH. Conclusions Subclinical LV systolic dysfunction was a frequent finding in this cohort of COPD patients, even in those with normal pulmonary artery pressure. Evidence of LV diastolic dysfunction was hardly present as measured by conventional echo indices.